Studies on the Effect of Starvation on Prolonged Callus Cultures and Alterations in SERK Gene Expression during Somatic Embryogenesis in Momordica charantia Linn. - Das, Subhasree; Talapatra, Shonima; Raychaudhuri, Sarmistha Sen (Plant Tissue Culture and Biotechnology, 2021)
Abstract not available Plant Tissue Cult. & Biotech. 31(1): 109-114, 2021 (June)